PENGGUNAAN MEDIA GAMBAR DALAM KETERAMPILAN MENULIS PUISI DI SEKOLAH DASAR - Tahta Qurotu A’yunina (Dirasah : Jurnal Studi Ilmu dan Manajemen Pendidikan Islam, 2018)
The learning process is basically demands the ability of teachers to control students' learning activities. Although not every learning activity, students rely on the presence of the teacher, but there is a causal relationship between teachers teach and students learn. Therefore, one of the responsibilities of teachers in the learning process is to design and implement the learning process in a way that students can achieve the goals that have been set. Creating an effective learning with the involvement of students in order to learn and grow going optimization of basic skills and complex skills in students, not an easy task. This requires another aspect that is not only verbal, but the inclusion of a variety of learning resources used by students with attendance and proper use. Therefore, it is necessary as part of the instructional media learning resources. Media helpful image to equip, maintain, and even improve the quality of ongoing learning, learning outcomes, activities, and student motivation. In the process of learning the presence of media images in poetry writing skills have to be particularly important because in the event that material submitted can deliver media as intermediary. This study focused on describing media images in poetry writing skills. This study aims to determine (1) the use of the techniques of media images in writing skills poetry in Islamic Elementary School Nurul Jadid, State Islamic Elementary School Kolomayan, and Islamic Elementary School Hashim As'ary Wonodadi Blitar, (2) to know the results of students in the use of media images in writing skills poetry in class V Islamic Elementary School Nurul Jadid, State Islamic Elementary School Kolomayan, and Islamic Elementary School Hashim As'ary Wonodadi Blitar. (3) To find out the constraints encountered in the use of media images in writing skills poetry Islamic Elementary School Nurul Jadid, State Islamic Elementary School Kolomayan, and Islamic Elementary School Hashim As'ary Wonodadi Blitar. This study used a qualitative descriptive approach to the type of multi-case. The subjects were students of class V Islamic Elementary School Nurul Jadid, State Islamic Elementary School Kolomayan, and Islamic Elementary School Hashim As'ary Wonodadi Blitar. The data source consisted of informants, participants, locations, documentation. Data collection techniques by observation, in-depth interviews, and documentation. Analysis of data using data analysis in the case and cross-case analysis of the data. While checking the validity of the data using focus peers, data triangulation, and triangulation of data sources. From these results, the authors concluded that (1) the use of technical implementation of media images in writing skills poetry in class V Islamic Elementary School Nurul Jadid, State Islamic Elementary School Kolomayan, and Islamic Elementary School Hashim As'ary. material that is difficult / abstract always use a medium of learning and practice for more simplicity, most media image media, direct objects and works of learners, to form an interesting learning invites students to the library, the school environment, to the outdoors, such as rice paddies, rivers and the ground. Techniques used lectures, media images, but it invites children to observe pictures that were in the school environment. (2) the results of students in the use of media images in writing skills poetry in class V Islamic Elementary School Nurul Jadid, State Islamic Elementary School Kolomayan, and Islamic Elementary School Hashim As'ary. Increase enthusiastic learners, enhance creativity and imagination of students, results of using the media image is very good. Learners' achievements can be increased more than if not using the media. (3) the constraints faced in the use of media images in writing skills poetry Islamic Elementary School Nurul Jadid, State Islamic Elementary School Kolomayan, and Islamic Elementary School Hashim As'ary prepare the medium, time constraints usage, the image must be in accordance with the theme of the picture, no Wi-Fi or internet, elections words (diction).